The partition dimension of origami graphs and its barbell - Luthfia Ayu Fakhira; Nur Wafiqoh Hadi; A. Asmiati; Dina Eka Nurvazly (Indonesian Journal of Combinatorics, 2025)
The origami graph, On, n≥3, is a graph formed by a central cycle with origami folds, where each fold consists of two C3 cycles. The barbell origami graph, BOn for n≥3 is obtained by copying a On and connecting two graphs with a bridge. In this research, we determined the partition dimension of the origami graphs and its barbell.